Kepemimpinan dalam Perspektif Ki Hajar Dewantara dan Implikasinya Terhadap Praktik Kepemimpinan Pendidikan di SMA Taman Madya 1 Jakarta Pusat - Bagus Prasetyo Heru Herlangga; EE Junaedi Sastradiharja; Agus Tasbih (Jurnal Global Ilmiah, 2026)
This study aims to analyze the leadership principles of Ki Hajar Dewantara and their implications for educational leadership practices at SMA Taman Madya 1 Central Jakarta. Using a descriptive qualitative approach, the research explores the application of the concepts ing ngarso sung tulodo, ing madya mangun karso, and tut wuri handayani in the school’s managerial and pedagogical processes. The findings indicate that Ki Hajar Dewantara’s leadership values are integrated into the principal’s leadership style through exemplary behavior, empowerment of school members, and support for the independence of teachers and students. These principles contribute to strengthening collaborative work culture, enhancing character development, and creating a humanistic and participatory learning environment. The study affirms the relevance of Ki Hajar Dewantara’s thoughts in shaping educational leadership based on ethics, wisdom, and humanity.